2016
DOI: 10.1186/s12885-016-2359-1
|View full text |Cite
|
Sign up to set email alerts
|

Activated thrombin-activatable fibrinolysis inhibitor (TAFIa) attenuates breast cancer cell metastatic behaviors through inhibition of plasminogen activation and extracellular proteolysis

Abstract: BackgroundThrombin activatable fibrinolysis inhibitor (TAFI) is a plasma zymogen, which can be converted to activated TAFI (TAFIa) through proteolytic cleavage by thrombin, plasmin, and most effectively thrombin in complex with the endothelial cofactor thrombomodulin (TM). TAFIa is a carboxypeptidase that cleaves carboxyl terminal lysine and arginine residues from protein and peptide substrates, including plasminogen-binding sites on cell surface receptors. Carboxyl terminal lysine residues play a pivotal role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 50 publications
(57 reference statements)
1
11
0
Order By: Relevance
“…We were also interested in other hub genes that may play an essential role in tumor stromal cell infiltration, although they are not associated with patients' survival. F2, which encodes the coagulation factor II (also known as thrombin), is a pro-inflammatory and pro-coagulant molecule that is elevated in various cancers, including breast and gastric cancers [46,47]. Recent studies showed that disorders of the coagulation-fibrinolysis system are associated with the efficacy of immune-checkpoint inhibitors [48].…”
Section: Discussionmentioning
confidence: 99%
“…We were also interested in other hub genes that may play an essential role in tumor stromal cell infiltration, although they are not associated with patients' survival. F2, which encodes the coagulation factor II (also known as thrombin), is a pro-inflammatory and pro-coagulant molecule that is elevated in various cancers, including breast and gastric cancers [46,47]. Recent studies showed that disorders of the coagulation-fibrinolysis system are associated with the efficacy of immune-checkpoint inhibitors [48].…”
Section: Discussionmentioning
confidence: 99%
“…Increased pericellular plasmin formation due to uPA released by endothelial and inflammatory cells results in facilitation of vascular remodeling via enhanced extracellular matrix degradation and augmented vascular cell migration. TAFIa may attenuate uPA-mediated pericellular plasmin formation by cleavage of C-terminal lysines from partially degraded fibrin (51) and plasminogen receptors (35,52). Some of the protective effects of the anti-uPA antibody may be independent of TAFI, however, as thrombin-mediated inactivation of single chain uPA may also be reduced in hemophilia (53); this cannot be distinguished in the current study.…”
Section: Discussionmentioning
confidence: 75%
“…Loss of TAFIa activity in hemophilia was recently found to promote joint bleeding due to unopposed uPA-mediated activation of plasminogen (28), which is normally attenuated by TAFIa due to the removal of C-terminal Lys from partially degraded fibrin (31,32). In addition, TAFIa has antiangiogenic effects on endothelial cells (33), reduces migration and invasion of breast cancer cells (34,35), and attenuates the formation of abdominal aorta aneurysms in vivo (36), which was ascribed to its ability to reduce extracellular matrix degradation by suppressing plasmin formation. TAFIa also provides protective antiinflammatory effects in various mouse models of arthritis by reducing synovitis and cartilage destruction, and this primarily involves inactivation of the complement anaphylatoxins C3a and C5a, and of thrombin-cleaved osteopontin by removal of their C-terminal Arg (37)(38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…This thrombin activity has been related to cancer and metastasis. The inhibition of these enzyme would be associated to increased cell metastatic behavior [32], which indicates that cellular movement is one of the regulated processes in myticin C-treated hemocytes. Cellular mobility implies conformational changes of the actin cytoskeleton [33].…”
Section: Discussionmentioning
confidence: 99%